The Return of Sense on the Scene of Translation Studies in the Light of the Cognitive Blending Theory - Fougner Rydning, Atin (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2005)
AbstractThe aim of this paper is to revitalize the Paris school model of deverbalization and reverbalization of sense in translation, i.e. the representation of sense as a mental image, in light of the cognitive blending theory. Through sample examples of online process data taken from the concurrent think-aloud protocols of two experienced professional translators and the keylogged files on their writing processes, I will give evidence of the imaginative and creative work pertaining to their construals of sense, before showing that the blending theory model represents sense as the result of mapping concepts into other concepts and as relations between mental spaces.